ANALISIS PENGARUH CURRENT RATIO, RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Transportation Services Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Ulmiasari, Anggi Mega, Jati Waskito,SE., M.Si (2016)
This study aims to determine and prove whether the Current Ratio (CR), Return on Assets (ROA) and Return On Equity (ROE) effect on stock prices on transportation services company listed on the Indonesia Stock Exchange in 2011-2014. Researchers used a sample of 31 companies transportation services selected by purposive sampling. The data used in this study are the financial statements issued by the Indonesian Capital Market Directory (ICMD) and IDX Yearly Statistics. The data are taken in the form of financial statements transportation services company listed on the Indonesia Stock Exchange in 2011-2014. The variables in this study using a variable Current Ratio, Return on Assets, Return on Equity as an independent variable and stock price as the dependent variable. The analysis technique used is multiple linear regression analysis, t-test, F, and the coefficient of determination. In conclusion, the variable Current Ratio, Return on Assets, no significant positive effect on stock price, while Return on Equity significant negative effect on stock price. Variable Current Ratio, Return on Assets, Return on Equity simultaneously not significant effect on stock price. Keywords: Current Ratio, Return on Assets, Return on Equity, Stock Price